Diagnostic Challenge: Sequential Unilateral Cranial Neuropathies Due to Perineural Spread of Carcinoma. (4th July 2017) - Moss, Heather E.; MacIntosh, Peter W.; Slavin, Konstantin V.; Collins, John M.
ABSTRACT: An 86-year old man developed sequential dysfunction of trigeminal (V1), facial, abducens, trigeminal (v2), oculomotor, and hypoglossal cranial nerves on the right over 20 months. Magnetic resonance imaging (MRI) showed a lesion in the right cavernous sinus. Although there was clinical suspicion that this was related to perineural spread of an extracranial tumour, a primary lesion was not discovered. Stereotactic biopsies of the intracranial lesion were non-diagnostic, and the patient succumbed to his tumour following a period of rapid growth. Postmortem examination showed the intracranial lesion to be a carcinoma with squamous features. This case highlights the challenges of diagnosis of intracranial perineural spread and the potential for transformation from indolent to aggressive tumour behaviour.